Ketertarikan Anaxipha longipennis Serville (Orthoptera: Gryllidae) terhadap Beberapa Jenis Gulma di Sawah sebagai Tempat Bertelur - Sri Karindah; Ardiyanti Purwaningsih; Anis Agustin (Jurnal Entomologi Indonesia, 2011)
Anaxipha longipennis Serville (Orthoptera: Gryllidae) is one of the generalist predator in rice habitat that has a potential as a biological control agents of rice leaf folder eggs and small insects such as rice hoppers. Females insert their eggs in plant tissue. The female’s oviposition site is important for the subsequent distribution of the cricket. Oviposition preference on 17 weeds species from rice habitat were tested in a free choice experiment in the laboratory. There was strong evidence to conclude that the cricket preferred certain plant for laying eggs. In free choice experiment nine species of weeds were preferred by A. longipennis for laying their eggs instead of rice. The preferred species were ranked as follows: rice, Monochoria vaginalis, Cyperus rotundus, C. iria, Echinochloa colonum, E. crusgalli, Eleusine indica, Fimbristylis miliacea, Imperata cylindrica, and Limnocharis flava. Whereas Ageratum conyzoides, Alternanthera sessilis, Commelina diffusa, Leersia hexandra, Leptochloa chinensis, Ludwigia adscendens, Panicum repens, and Sonchus arvensis were not preferred in free-choice test.